Plasma Nitriding Performed under Atmospheric Pressure using Pulsed-Arc Plasma Jet - Ichiki, R.; Nagamatsu, H.; Yasumatsu, Y.; Yoshida, M.; Akamine, S.; Kanazawa, S. (International Conference on Plasma Surface Engineering, 2013)
Plasma nitriding is achieved by spraying the nitrogen pulsed-arc plasma jet under atmospheric-pressure N2/H2 mixture. The quality of nitriding is found to depend on the H2 flow rate, which has an optimal value. We propose a simple mechanism of this dependence. Moreover, the amount of H2 necessary for best nitriding can be decreased to 1/20 by changing the way of H2 addition.